A Modelling Study on Visitor Usage Intentions with AR-Based Content for Sports Venues - Ni Eun Song; Eun Joung Kim, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This study examined the development of users' behavioural intentions to visit sports venues when using AR-based content using the stimulus-organism-response model. The study centred on individuals who had experienced the AR-based content at Gocheuk Sky Dome. This study presents a structural model that illustrates the connections between three attributes of Augmented Reality (AR)—interactivity, vividness, and novelty (stimulus)—and their influence on the flow experience. This, in turn, affects the intention to depend on AR-based content for visiting a sports venue. A survey was conducted to evaluate the model, targeting young visitors in their 20s and 30s who are knowledgeable about AR technology. The study's findings indicate that novelty had the greatest influence on flow, followed by vividness, while interactivity did not show any significant impact. Flow had a significant impact on all four experiences: education, entertainment, aesthetics, and escapism. The positive impact on the intention to visit AR-based sports venues was observed only in relation to entertainment and education experiences. The role of consumer cultural innovativeness was examined as a moderator in the proposed structure model for visiting AR-based sports venues. These insights offer valuable information for the development of AR-based content in countries with culturally significant tourist destinations for sports enthusiasts. They also guide destination marketers in promoting AR in the tourism industry.